IMPROVING STUDENTS’ WRITING SKILLS THROUGH MIND MAPPING TECHNIQUE INTEGRATED WITH PICTURE SERIES - Predi - Gantara (Politeknik Negeri Bengkalis, 2022)
The present research aimed at finding out how mind mapping using picture series improved students’ writing skills and how it can encourage students’ interest in teaching and learning process. To reach the aims of the research, the present research used a classroom action research.There were 17 participants in the research which consisted of 8 females and 9 males of Bussiness Management Study Program Students at Darwan Ali University Unit II. The present research was conducted in two cycles. Cycle I had three meetings and the second II had two meetings. In this classroom action research, the researcher conducted the plan, action, observation, and reflection.The results of the finding showed that (1) The application of mind mapping using picture series can improve students’ skill based on the calculation of the percentage, the students who achieved score 65 and more were 100 %. It was higher than 80%; (b) Mind mapping using picture series made the students interested to learn English writing. Before the actions were conducted, the students were less motivated in the teaching and learning process. After the implementation of the actions, they were more enthusiastic to get involved in the teaching and learning process. They became active and paid attention during the lesson. Besides, the students were autonomous in learning without depending on their friend’s works in doing the tasks.